Gender Segregation in the Russian Banking Sector: Board of Directors Composition Analysis - Yelena Yu. Prosvirkina (Ural State University of Economics, 2018)
The paper studies gender composition of the board of directors of Russian banks. In the course of the study, the authors analyse the data provided by fifty large Russian banks. We collected the data from the banks’ official websites and used public information on the Russian banking sector. The article reviews theoretical works on the subject matter, describes the research method and presents the results of empirical testing. The study finds that representation of women in the board of directors in the Russian banking sector is still low and amounts to approximately 10–20%. At the same time, the percentage of female members in the Russian offices of international banks is higher compared to local banks. The analysis of qualifications of female and male members of the board of directors shows that women possess the same level of education and work experience as men. Based on the results of international empirical studies, we make an assumption that increased representation of women in the boards of directors of Russian banks can help to produce better financial results.